FAKTA DAN OPINI PADA TAJUK RENCANA “HARIAN ANALISA” TAHUN 2020 - Khanati Gulo; Merri C. Zalukhu; Anita Zagoto (Kohesi : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research is motivated by the uniqueness. One of the unique things found in the "Analysis Daily" newspaper in 2020, among others, is that the newspaper has an editorial column. Which in this editorial news has similarities or mutually supportive harmony between facts and editorial ideas, so that in harmony makes readers more interested in reading the news because the opinions conveyed by the editors are in accordance with the facts that actually happened. In addition, the researcher saw and found that in newspapers, especially editorials, there were a lot of news in the form of facts and opinions. The purpose of this study is to describe the content of factual news in the 2020 editorial "Harian Analys", to describe opinions in the 2020 editorial "Harian Analys", and to describe the correspondence between facts and opinions in the 2020 editorial "Harian Analysis". This study uses a qualitative approach with a descriptive method. The results of the study show that in the 2020 "Daily Analysis" editorial, there are 61 facts and 74 opinion quotes. Conformity between facts and opinions in the 2020 “Daily Analysis” Editorial, namely having similarities and mutually supportive harmony between facts and editorial ideas.So the summary of facts and opinions in the 2020 editorial “Daily Analysis” is more opinion than facts. The data of the findings of this study can be implied in everyday life, namely as reference material or guidelines in understanding news content for the news reader community. In addition, the research findings can be used by teachers as reference material in learning for students at school, especially for high school students. In this way, students are able to know and distinguish between factual news and news that are still in the form of opinions.